Development of augmented reality-based interactive space media for 5th grade elementary school students - Triwahyuningtyas, Dyah; Ningrum, Siska Widyana; Suastika, I Ketut; Azizah, Nurul (Universitas Kanjuruhan Malang, 2025)
This research is motivated by the lack of interactive learning media in schools. The study aims to determine the feasibility of Augmented Reality-based interactive space building media using the Assemblr EDU application for 5th grade elementary students. This development research applies the ADDIE model with data collected through observation, interviews, documents, and questionnaires. The research subjects involved 14 students from SDN Sukun 1 Malang. The study focuses on the feasibility aspect based on expert validation. The results show that media experts gave a feasibility percentage of 98% in the